A Contextual Analysis of Inaugural Speeches of Sierra Leonean And Gambian Presidents - Esther, Robbert; Udeme Emmanuel, Udoh (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This paper is an exploration and contextual analysis of political discourse. It examines the power of language in political speeches and how power and influence are expressed in language within the appropriate context. The theoretical framework used in the analysis of the data is pragmatic context. It analyses ten utterances randomly selected from the inaugural speeches of the Sierra Leonean President, Julius Maada and the Gambian President, Adama Barrow. The work discovers that political utterances are made in context of the people’s expectations, desires and hope for a better government. With this in view, the utterances hinge on the psychological state of the governed. They are aimed at elating their desires and the psychological satisfaction that their choice of personnel in government will live up to expectations. The paper concludes that both speeches are filled with persuasive and enticing words which promise a reformation in governance, improved condition of living and sustainable development as idealized in the minds of the governed. These utterances bring psychological relief and satisfaction which may be sustained in fulfilment of the promises or dashed.